DAMPAK PENGARUH PEMBIAYAAN MURABAHAH TERHADAP PERKEMBANGAN UMKM SELAMA PANDEMI COVID-19 - Dhoqi Dofiri; Istianah Istianah; Ridan Muhtadi (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2021)
Introduction: The background of study is stimulated by the existance of micro-financing by using al-murabahah agreement at PT BRI Syariah branch of Bangkalan which is distributed to business people on level of medium, small and micro who need loan as the additional venture capital. Based on the explanation above, the research problems are; the condition of UMKM customers at BRI Syariah, especially the bangkalan people and the influence of Murabahah financing conducted by BRI Syariah on UMKM people in Bangkalan Methods: The study applies the quantitative design in which the data collecting technique used are documentation, interview and questionnaire. Data analysis and processing technique used are SPSS which consist of simple linear regression, correlation test, t-test and excel percentage. The implementation time of this research was carried out in October 2020. Results: The result of the study are: (1) the actors of medium, small and micro business level in bangkalan have taken the murabahah financing at PT. BRI Syariah branch of Bangkalan as the additional venture capital that they has run, and (2) murabahah financing at PT. BRI Syariah branch of Bangkalan is very influential on the development of UMKM people in Bangkalan. It can be measure by the increasing of the income as 236%. Keywords: Micro, Small and Medium Enterprises (MSMEs), al-murabahah finance, income, UMKM development.